Efficient mobile video transmission based on a joint coding scheme - Azni, Mohamed; Boudjadja, Rima; Dahmani, Abdelnasser; Zennir, Mohamed Nadjib (Universiti Utara Malaysia Press, 2017)
In this paper, we propose a joint coding design which uses the Symbol Forward Error Correction (S-FEC) at the application layer. The purpose of this work is on one hand to minimize the Packet Loss Rate (PLR) and, on the other hand to maximize the visual quality of video transmitted over a wireless network (WN).The scheme proposed is founded on a FEC adaptable with the semantics of the H.264/AVC video encoding.This mechanism relies upon a rate distortion algorithm, controlling the channel code rates under the global rate constraints given by the WN.Based on a data partitioning (DP) tool, both packet type and packet length are taken into account by the proposed optimization mechanism which leads to unequal error protection (UEP). The performance of the proposed JSCC unequal error control is illustrated over wireless network by performing simulations under different channel conditions. The simulation results are then compared with an equal error protection (EEP) scheme.